Generation of myeloid-derived suppressor cells mediated by microRNA-125a-5p in melanoma - Lasser, Samantha; Özbay Kurt, Feyza Gül; Fritz, Lennart; Gutzeit, Nina; Torre, Carolina de la; Altevogt, Peter; Utikal, Jochen; Umansky, Viktor (International journal of molecular sciences, 2024)
The ability of tumor-derived extracellular vesicles (EVs) to modulate the function of myeloid cells is widely recognized. Hence, a comprehensive understanding of the distinct components associated with EVs and the signals that they deliver to myeloid cells could provide potential approaches to impede the immunosuppression by myeloid-derived suppressor cells (MDSCs). We investigated melanoma EV-associated microRNAs (miRs) using the RET transgenic melanoma mouse model and simulated their transfer to normal myeloid cells by transfecting immature mouse myeloid cells and human monocytes. We observed elevated levels of miR-125a-5p, -125b-5p, and let-7e-5p in mouse melanoma-infiltrating MDSCs. In addition, miR-125a-5p levels in the tumor microenvironment correlated with mouse melanoma progression. The delivery of miR-125a-5p, alone or in combination with let-7e-5p and miR-99b-5p from the same genomic cluster, to normal myeloid cells resulted in their conversion to MDSC-like cells. Our findings indicate that miR-125a-5p could modulate myeloid cell activation in the melanoma microenvironment via a NF-κB-dependent mechanism.